Digital Libraries and Multimedia - Bhargava, Bharat (Springer US, 2002)
Digital Libraries and Multimedia brings together in one place important contributions and up-to-date research results in this fast moving area. Digital Libraries and Multimedia serves as an excellent reference, providing insight into some of the most challenging research issues in the field.